Association of genotypes at promoter region of lactoferrin gene with mastitis in crossbred cattle - Rahmani, S F; Jayashankar, M R; Nagaraja, C S; Bhaskaran, R; Byregowda, S M; Satyanarayan, K (The Indian Journal of Animal Sciences, 2012)
Mastitis inflammation, a cellular reaction to the irritant occurs. Lactoferrin is a component of the natural protection systems of human and animals. We investigated whether lactoferrin gene polymorphism is associated with mastitis. Blood samples were collected from 124 HF crossbred cattle under lactation from organized farms and field from Bengaluru district of Karnataka. The animals were examined for the presence of mastitis using California mastitis test, and separated into mastitis positive and mastitis negative groups. Oligonucleotide primers were used to amplify a 1049 bp long fragment corresponding to the promoter Lactoferrin locus. The amplified products were subjected to PCR-RFLP technique using Hinf1 restriction enzyme. The Hinf I digestion produced 2 genotypes. The frequency of genotype AA was higher in mastitis free group, while the frequency of genotype BB was higher in mastitis group. Nucleotide sequence was submitted to the NCBI and released on public data base (Accession number HQ676491.1). The study revealed the polymorphism at the Lactoferrin gene promoter locus, can be used as a marker of susceptibility/resistance to mastitis in dairy cattle.